A comprehensive study on electricity utilization and CO2 emissions in Sami Laris Swalayan, Cilacap, Indonesia - Yuliani, Aulia Rachma; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Indonesian Journal of Applied Environmental Studies, 2024)
In today's world, with an increased focus on environmental awareness and sustainability, mitigating carbon footprint has emerged as a crucial goal for businesses across various sectors, including supermarket chains. This research centers on Sami Laris Swalayan, a prominent and widely recognized supermarket chain, to comprehensively analyze its electricity utilization patterns and the corresponding carbon dioxide (CO2) emissions. By delving into electricity utilization data spanning a specific period, this study identifies peak demand periods, explores energy-efficient opportunities, and assesses the potential for integrating renewable energy sources. The research underscores the significance of reducing CO2 emissions, advocating sustainable energy practices within the supermarket chain, contributing to environmental conservation efforts, and fostering a culture of responsible energy management. The investigation begins with a thorough analysis of Sami Laris Swalayan's electricity utilization, seeking to understand the varying trends and patterns in energy consumption. The data above shows the fluctuating electricity consumption of the company, with the highest figure recorded in April, reaching 26,965 kWh. The high electricity usage is attributed to the total operational hours from 09:00 to 21:00 and the addition of other facilities such as the accessory room, bakery outlet, and coffee outlet. In contrast, the lowest consumption was observed in February, with 23,796 kWh, which was influenced by the implementation of Large-Scale Social Restrictions (PSBB) at the end of January 2021. During this period, the operational hours were shortened from 09:00 to 19:00, leading to a decrease in electricity consumption the following month. ABSTRAK Dalam era modern ini, dengan fokus yang semakin meningkat pada kesadaran lingkungan dan keberlanjutan, mengurangi jejak karbon telah menjadi tujuan krusial bagi bisnis di berbagai sektor, termasuk rantai supermarket. Penelitian ini berfokus pada Sami Laris Swalayan, sebuah rantai ...